Success of the Undergraduate Public Health at Tulane University - White, Luann Ellis (Frontiers in Public Health, 2015)
Tulane University School of Public Health and Tropical Medicine (SPHTM) launched the Bachelors of Science in Public Health (BSPH) in 2005. The BSPH has steadily grown and comprises one third of the total enrollment in the school. A review of the organizational structure demonstrates that direct responsibility for undergraduate education by a school of public health is advantageous to the success of the program. The competency and skills-based curriculum attracts students. Outcome measures show the enrollment is steadily increasing. The majority of the BSPH graduates continue onto competitive graduate and professional degree programs. Those who seek jobs find employment related to their public health education, but outside of the traditional governmental public health agencies. The combined BSPH/MPH degree is a pipeline for students to pursue a MPH and increases the likelihood students will pursue careers in public health. The range and depth of study in the bachelors program is continually examined. Topics once within the purview of graduate education are now being incorporated into undergraduate courses. Undergraduate public health is one of a number of factors that is influencing changes in the MPH degree.